(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
When substantiating decisions on the spatial organization of the economy, consideration of the influence of the safety factor is necessary, as the development of civilization is accompanied by various threats. Safety – the state in which the impact of threats can be reduced to an acceptable level, and the consequences of their influence – to eliminate. Types of economic activity that are sensitive to a safety factor, when placed should be guided by the appropriate places that become for such industries in possible placement (IPP). In this case, the security factor may be dominant (when, in order for the site to become IPP, it is sufficient to be safe) or to influence the group of factors. The security factor influences the spatial organization of the economy by forming the boundaries of the scope of analysis, the state policy of restrictions on the location of economic activity, the state policy of placement and encouragement of the placement of economic activity, the formation of a list of IPP taking into account the safety factor. The directions of the impact of the security factor on spatial organization of the economy include restrictions on production capacity, which are established by the state or arising from other reasons, certain types of economic activity in certain places. It is substantiated that the process of formation of the list of IPP products from the point of view of the factor of safety should provide the following logical sequence: 1. Formation of a list of technologies that can be used for the production of estimated products. Separate technology and manufactured products form a separate product group (SPG); 2. Establishment of the boundaries of the analysis space, within which searches will be made of the optimal places of production, taking into account the safety factors (national, technogenic and ecological, etc.) for each technology from the current list. Since different SPG can be characterized by different analysis spaces, setting boundaries for this case will require a separate solution. Since the analysis space may be different for different types of security – this should also be taken into account when setting boundaries; 3. Within the established area of analysis for each SPG, places are defined which, from the point of view of safety of the placement of the estimated type of economic activity is not permissible. At the same time, it should be taken into account the suitability of the place of the destructive effects of nature and the dangerous effects of human activity, as well as the possible negative impact of the estimated type of economic activity on the ecological and socioeconomic systems; 4. Within the defined area of analysis for each SPG, IPP of the production of the assessed products are established taking into account the safety factor and other factors specific to the corresponding SPG. Among the IPP there may be existing places of production of estimated products; 5. Justification of the choice of optimal technology for each IPP (competition of technologies in the IPP) provided that the level of product safety is reached, taking into account the permissible production capacity of the product at that location, using the appropriate technology. For each existing production site, simultaneously with new technologies, the existing technology will be considered; 6. Selected technologies (optimal for the corresponding IPP) will be compared by economic indicators (competition of technologies at a distance). IPP, where the technology lost the competition at a distance, are considered unpredictable for the production of estimated products. IPP, where technologies have not lost competition at a distance, are considered promising for the production of evaluated products; 7. Prospective IPP are evaluated according to the criterion of the size of the sales market. If the size of the sales market exceeds the minimum acceptable level, then the promising IPP is considered to be positively evaluated by the criterion of the size of the sales market; 8. IPP, positively evaluated by the criterion of the size of the market, are recommended as places of expedient placement of the production of estimated products with a capacity that corresponds to the predetermined size of the market, but does not exceed the permissible. Further studies on the impact of the safety factor on the spatial organization of the economy are promising in the direction of developing a methodology for identifying types of economic activity, the location of which depends on the safety factor, as well as solving problems associated with the establishment of the boundaries of the analysis space for different groups of production and various factors security with non-identical analysis space.